SEXUALITY AND MONOGAMY: UNEARTHING MELODRAMA FORMULA IN ALICE SEBOLD’S "THE LOVELY BONES" - Zuhrul Anam; Imas Istiani (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2021)
Every popular literature has a particular formula for certain intrinsic elements such as favorite plots, stereotyped characters, and accepted ideas. Therefore, the genre is widely accepted by readers. It represents familiar shared images and meanings that assert an ongoing continuity of values. Therefore, this study aims: (1) to elucidate the kind of melodrama formula used that makes a novel popular and widely accepted, and dramatizes moral value shared by its readers, and (2) to make justification on the cultural behavior or universal pattern that may underline its popularity. The object of the study is The Lovely Bones by Alice Sebold. Descriptive analysis is used to explore the data with the Concept of Formula by Cawelti that serves as the theory. Based on the data analysis, the conclusions draw as follows. First, conventions and inventions of the social melodrama genre are used to dramatize sexuality in which it’s identified through the theme. Second, this shared moral value turns from traditional religious into the secular humanist world. However, this change remains to defense a monogamous life and family-oriented relationship.